Disruption of SHP1/NMDA receptor signaling in spinal cord dorsal horn alleviated inflammatory pain. (15th July 2018) - Yang, Li; Bai, Hu-Hu; Zhang, Zi-Yang; Liu, Jiang-Ping; Suo, Zhan-Wei; Yang, Xian; Hu, Xiao-Dong
Abstract: Src-homology 2 domain-containing protein tyrosine phosphatase-1 (SHP1) is one of the non-receptor-like phosphatases that are highly enriched in hematopoietic cells. Although accumulating evidence has implicated the protein tyrosine phosphatases in the regulation of nociceptive transmission and plasticity, it is largely unknown whether SHP1 was expressed in pain-related spinal cord dorsal horn and engaged in the synaptic modification of nociceptive signals. Here we found that SHP1 was present in spinal neurons of rats and functionally coupled to GluN2A subunit-containing N-methyl-d -aspartate subtype of glutamate receptors, one of the key players in central sensitization of nociceptive behaviors. SHP1 interacted with a membrane-proximal region within the cytoplasmic tail of GluN2A. This interaction was necessary to stimulate SHP1 activity and more importantly, restrict SHP1 signaling to specifically enhance the tyrosine phosphorylation of GluN2A during inflammatory pain. Electrophysiological and behavioral studies showed that SHP1 binding potentiated GluN2A currents and evoked GluN2A-dependent pain hypersensitivity. The siRNA-mediated knockdown of SHP1 or interference with SHP1/GluN2A interaction by a synthetic peptide alleviated inflammatory pain induced by either Complete Freund's Adjuvant or formalin. Our data implicated that SHP1 was a specific enhancer of GluN2A-mediated nociceptive synaptic transmission in spinal cord dorsal horn, and manipulation of SHP1 activity may serve as an effective strategy for the treatment of inflammatory pain. Highlights: SHP1 specifically interacted with GluN2A subunit-containing NMDA receptors. SHP1 activity regulated GluN2A currents. Peripheral inflammation stimulated SHP1/GluN2A signaling in spinal dorsal horn. Disturbing SHP1/GluN2A interaction alleviated inflammatory pain.